PENGARUH NILAI-NILAI KERJA, KEMAMPUAN KOMUNIKASI DAN PENANGANAN KELUHAN TERHADAP KEPUASAN MASYARAKAT DALAM PELAYANAN RSUD SERANG - Arenawati Arenawati (Universitas Sultan Ageng Tirtayasa, 2010)
This study aims to determine how much influence the work values of service satisfaction, how much influence the ability of communication to the satisfaction of service, how much influence the handling of complaints against the satisfaction of service, how much influence the values of work, communication skills and handling of complaints against the service satisfaction. This research was undertaken at The Regional Public Hospital of Serang. This research is a quantitative survey research method with a view to doing an explanation. Methods of data collection using questionnaires, unstructured interviews, informal observations, and documentation. The analysis method is quantitative analysis with statistical tests include: frequency distribution, product moment correlation, partial correlation, multiple correlation, simple linear regression, and multiple regression. Number of study samples as many as 280 respondents. Results showed: (1) Working Values has a positive and significant impact on service satisfaction by 0.554, (2) Communication Ability has a positive and significant impact on service satisfaction by 0.470 (3) Handling of Complaints has a positive and significant impact on service satisfaction by 0.585. (4) Work Values, Communication Skills and Handling Complaints has a positive and significant impact on service satisfaction by 0.592./